Correlates of Informal Grievance Resolution Among Fist-Line Supervisors - Knight, Thomas (Relations industrielles / Industrial Relations, 1986)
This study analyzes the influence on the rate of informal grievance resolution of differences in experience and interaction with union and other management officers of a sample of first line supervisors